Implementation of immunohistochemical staining among mohs micrographic surgeons. Issue 2 (28th April 2022) - Sarlin, Samantha K.; Beroukhim, Kourosh; Tarantino, Isadore; Goldberg, Leonard H.; Kimyai‐Asadi, Arash
Abstract: Background: Immunohistochemical staining has been used as part of Mohs micrographic surgery (MMS) to improve sensitivity for the detection of subtle residual tumors. It is typically used in the histopathologic detection of tumors such as malignant melanoma, extramammary Paget disease, and poorly differentiated and spindle cell neoplasms. Materials and Methods: The study involved a questionnaire link emailed by the American College of Mohs Surgery to its members. The survey sought demographic information and asked about the use of immunohistochemistry (IHC) stains during fellowship training and in current practice as well as reasons why IHC staining is not incorporated into certain practices. The data were tabulated and analyzed. Results: A total of 84 surveys were completed. Of these, 30 (35.7%) indicated having received training in IHC during the fellowship, whereas 54 (64.3%) did not. Currently, 32 (38.1%) respondents utilize IHC in their practice, whereas 52 (61.9%) do not. Among those who trained in IHC during the fellowship, 60% ( n  = 18) continue to utilize IHC, whereas among those whose fellowship did not incorporate IHC, 74.1% ( n  = 40) do not utilize IHC. A number of different immunostains were reportedly utilized during fellowship and in current practice. Among those not utilizing IHC, the top reasons cited were lack of sufficient volume to justify use ( n  = 38, 70.3%), cost of implementation ( n  = 38, 70.3%), the stains being time‐consuming ( n  = 36, 66.7%), and lack of familiarity with reading immunohistochemical stains ( n  = 29, 53.7%). Conclusions: The use of IHC among Mohs surgeons appears to be rising compared to previous historical studies, but significant barriers remain to widespread implementation.